It is Only Natural : Europe's Low Interest Rates - Arena, Marco (IMF Working Papers; Working Paper, 2020)
Estimates of the natural interest rate are often useful in the analysis of monetary and other macroeconomic policies. The topic gathered much attention following the great financial crisis and the Euro Area debt crisis due to the uncertainty regarding the timing of monetary policy normalization and the future path of interest rates. Using a sample of European countries (including several members of the Euro Area), this paper provides estimates of country-specific natural interest rates and some of their drivers between 2000 and 2019. In line with the literature, our findings suggest that natural interest rates declined during this period, and despite a rebound in the last few years of it, they have not recovered to their pre-crisis levels. The paper also discusses the implications of the decline in natural interest rates for monetary conditions and debt sustainability.